Pengaruh Jumlah Anggota, Volume Usaha Dan Likuiditas Koperasi Terhadap Permintaan Jasa Audit Pada Koperasi Di Kabupaten Kampar - Rafika Sary; Restu Agusti; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The current need for reliable financial statements, and can be trusted is necessary in making a decision. The problem in this study is whether which the numberof members, the business volume and liquidity affect the demand for audit service. The population in this study were 182 cooperatives and the research sample is 87 cooperatives in Kampar. the dependent variables in this study are demand audit services. While the independent variables are the number of members, the business volume and liquidity of cooperatives. The data used in form of cooperative financial reports in fiscal year 2012 with using descriptive analysis, multicolonearitas and logistic regression with SPSS version 21. The conclusion of this research is variable business volume and liquidity affect on demand for audit services, while number of members does not influence the audit service.Keyword: number of members, business volume, liquidity, audit